Security and Sustainable Development in Myanmar - James, Helen (Routledge Contemporary Southeast Asia Series, 2006)
Helen James considers security in Myanmar/Burma. She uses the ideas put forward in the United Nations Development Programme's 1994 report, of human, as opposed to state and security, going on to argue that freedom from want, and freedom from fear (of the regime) are in fact mutually supportive ideas, and that the security of the people and the security of the state are in fact in a symbiotic relationship with each other. Presenting new and significant information of the security concept of Myanmar/Burma, James' original work considers economic development, health, education, environmental issues, the drugs trade, human rights, minority peoples and political, social and economic reforms, arguing that improved governance, the development of civil society and economic development would both strengthen the state and ensure the security and well-being of its citizens.